Impact of changes in the distribution of household types on residential energy consumption in Spain, 2006-2023 - Ramos Martín, Jesús; Matsumoto, Shigeru; Universitat Autònoma de Barcelona. Unitat d'Història Econòmica (2025)
Residential energy consumption remains challenging to analyze due to its heterogeneity and evolving demographic trends. Population aging and declining household sizes alter energy demand, potentially offsetting efficiency gains. However, most studies fail to disaggregate energy use by household type over time, creating a research gap in understanding how demographic changes impact residential energy demand. This study integrates demographic data from the Population and Housing Census with micro-level household energy consumption data from the Household Budget Survey (2006-2023). Using the Integrated Analysis of Demographic and Consumption Profile (IADCP) method, we quantify the impact of changes in household composition on energy demand. This approach allows us to isolate the effects of technological advancements, population growth, and shifts in household structure on energy consumption trends. Findings reveal that while technological advancements and behavioral changes have led to notable energy efficiency gains, demographic changes have largely offset these benefits, leading to an energy efficiency loss due to household composition change of 3.31%. The increase in the number of households has a more profound effect in the Mediterranean region, whereas changes in household composition, with smaller and older households, exert a greater influence in the North Atlantic region. This research contributes to energy policy by demonstrating the necessity of integrating demographic factors into efficiency strategies. Policies should prioritize energy-efficient housing, co-housing models, and behavioral interventions to mitigate the adverse effects of demographic shifts on residential energy demand.